Analysis Of Consumer Purchasing Decisions On PT. Hadji Kalla Toyota Car Sales Center In Makassar City (Toyota Avanza Car Case Study) - Gian Neysa Bulawan; Haris Maupa; Jusni Jusni (SEIKO : Journal of Management & Business, 2023)
This study uses quantitative research methods based on data from respondents that are processed manually using a formula based on the variables contained in this study. The data collection technique is done by using the best pyramid trigulation, namely, questionnaires, documentation, and observation. This study shows the variable sales of the Toyota Avanza used in variable measurement. The sales of the Toyota Avanza on the factors that influence consumers to buy a Toyota Avanza have a very large effect, this result shows unfavorable results because the level of sales has decreased every year. The benchmarks carried out on the sales of Toyota Avanza affect consumer factors in buying a Toyota Avanza car at PT. Hadji Kalla, Center for Toyota Car Sales in Makassar City because there are things that affect consumer interest in buying a Toyota Avanza car. Keywords: Toyota Avanza car sales, factors that influence consumers.